Comparative Chloroplast Genomes of Zosteraceae Species Provide Adaptive Evolution Insights Into Seagrass - Chen, Jun; Zang, Yu; Shang, Shuai; Liang, Shuo; Zhu, Meiling; Wang, Ying; Tang, Xuexi (Frontiers in Plant Science, 2021)
Seagrasses are marine flowering plants found in tropical and sub-tropical areas that live in coastal regions between the sea and land. All seagrass species evolved from terrestrial monocotyledons, providing the opportunity to study plant adaptation to sea environments. Here, we sequenced the chloroplast (cp) genomes of three Zostera species, then analyzed and compared their genome structure and sequence variations. We also performed a phylogenetic analysis using published seagrass chloroplasts and calculated the selection pressure of 17 species within seagrasses and nine terrestrial monocotyledons, as well as estimated the number of shared genes of eight seagrasses. The cp genomes of Zosteraceae species ranged in size from 143,877 bp (Zostera marina) to 152,726 bp (Phyllospadix iwatensis), which were conserved and displayed similar structures and gene orders. Additionally, we found 17 variable hotspot regions as candidate DNA barcodes for Zosteraceae species, which will be helpful for studying the phylogenetic relationships and interspecies differences between seagrass species. Interestingly, nine genes had positive selection sites, including two ATP subunit genes (atpA and atpF), two ribosome subunit genes (rps4 and rpl20), two DNA-dependent RNA polymerase genes (rpoC1 and rpoC2), as well as accD, clpP, and ycf2. These gene regions may have played key roles in the seagrass adaptation to diverse environments. The Branch model analysis showed that seagrasses had a higher rate of evolution than terrestrial monocotyledons, suggesting that seagrasses experienced greater environmental pressure. Moreover, a branch-site model identified positively selected sites in ccsA, suggesting their involvement in the adaptation to sea environments. These findings are valuable for further investigations on Zosteraceae cp genomes and will serve as an excellent resource for future studies on seagrass adaptation to sea environments.